RARE PRESENTATION OF OSTEOPOROSIS IN PREGNANCY: A CASE REPORT AND LITERATURE REVIEW - Kan, Meiji; Chua, Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Osteoporosis in pregnancy is a rare condition, with a reported occurrence of only 1.2% among individuals aged 20 to 40 years. Despite its infrequency, the condition carries significant potential for disability and adverse outcomes. CASE We present a 29-year-old female at 33 weeks of gestation, with a background history of type 2 diabetes mellitus with retinopathy. She, came in with a 5-week history of right hip pain. Subsequently, she fell from a standing position rendering her immobilized. A pelvic x-ray was performed, revealing a right femoral neck fracture. The patient had no history of steroid use. Initial investigations including thyroid function test, calcium and phosphate levels were within normal limits. However, serum parathyroid hormone was low at 0.95 pmol/L (normal range: 1.59-7.24) and vitamin D was low at 35 nmol/L (sufficiency >75). Following a Caesarean section, she underwent screw fixation of the neck of the right femur and was advised to refrain from weight-bearing on the affected limb for 3 weeks. Histopathological examination of the bone fragment revealed scanty bony trabeculae without atypical cells. A dual X-ray absorptiometry (DXA) scan revealed a normal bone mineral density (BMD) of the spine with Z-score of 0.1. The total left hip BMD was 0.673 g/cm3 with a Z-score of -1.7 and T score of -2.0. The fracture was attributed to a combination of factors, including vitamin D deficiency, hormonal changes during pregnancy and diabetes. The patient was started on calcium and vitamin D supplements. However, subsequent followups indicated non-union of the fracture with early avascular necrosis, necessitating referral to the arthroplasty team for further management. CONCLUSION This case underscores the importance of considering osteoporosis during pregnancy, especially among patients with comorbidities such as diabetes mellitus. Early recognition and adequate supplementations are paramount to mitigate complication of fracture.